2018
DOI: 10.1088/1361-6560/aac768
|View full text |Cite
|
Sign up to set email alerts
|

Neutron track length estimator for GATE Monte Carlo dose calculation in radiotherapy

Abstract: The out-of-field dose in radiation therapy is a growing concern in regards to the late side-effects and secondary cancer induction. In high-energy x-ray therapy, the secondary neutrons generated through photonuclear reactions in the accelerator are part of this secondary dose. The neutron dose is currently not estimated by the treatment planning system while it appears to be preponderant for distances greater than 50 cm from the isocenter. Monte Carlo simulation has become the gold standard for accurately calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…NTLE was used to determine neutrons that are part of the secondary dose. [13] Figures 3 and 4 show particle and dose distributions in brain tissue and out off-field global dosimetry.…”
Section: Resultsmentioning
confidence: 99%
“…NTLE was used to determine neutrons that are part of the secondary dose. [13] Figures 3 and 4 show particle and dose distributions in brain tissue and out off-field global dosimetry.…”
Section: Resultsmentioning
confidence: 99%
“…Among MC variance reduction techniques, track-length estimators are interesting scoring methods to get a fast and accurate MC simulation of rare events, as proposed back in the 80 s in the MNCP code (Forster and Godfrey 1985) and formalized for the evaluation of the photon dose with the Kerma approximation (Williamson 1987). In the past few years, several other variations of the TLE have been proposed, such as the neutron-induced gamma dose tally in GATE for radiotherapy applications (Elazhar et al 2018) and the next-event estimator in Tripoli-4 ® for neutron transport (Hutinet et al 2023). The PG source variation of the track-length estimator (vpgTLE) has also been proposed in GATE by (El Kanawati et al 2015) and a gain of about 1000 in relative uncertainty has been reported for a patient proton therapy treatment plan by (Huisman et al 2016).…”
Section: Introductionmentioning
confidence: 99%